RUU PERLINDUNGAN PEKERJA RUMAH TANGGA : KETIDAKPEDULIAN NEGARA DALAM MELINDUNGI HAK-HAK PRT DI INDONESIA - MUHAMMAD, NUR REGITA SAPUTRI (Ganec Swara, 2025)
The protection of domestic workers in Indonesia is an urgent and complex issue, given the significant number of domestic workers and their contribution to household welfare. However, the absence of clear regulations on domestic workers’ rights makes them vulnerable to exploitation, violence, and violations of basic rights. This study aims to analyze the impact of the lack of legal protection for domestic workers and the urgency of passing the Domestic Workers Protection Bill (PPRT). The analysis shows that without adequate regulations, domestic workers face a high risk of violence, inadequate wages, and lack of access to social security. In addition, social stigma and legal uncertainty further worsen their conditions. This research recommends the passage of the PPRT Bill as a crucial step to provide clear legal protection, increase public awareness of DWs’ rights, and strengthen the role of civil society organizations in advocacy. With these steps, it is expected that the welfare and protection of domestic workers can be significantly improved.